1955
DOI: 10.2172/4326597
|View full text |Cite
|
Sign up to set email alerts
|

ThO$sub 2$ SLURRY DEVELOPMENT: QUARTERLY REPORT FOR PERIOD ENDING APRIL 30, 1955

Abstract: I This mport was pmpred as an account of Government sponsorad work. Neither the United Stabs, nor the Commission, nor any person acting on behalf of the Commission: I A. Makes any wrmnty or representation, express or implied, with respect to the accumcy, wmpletenex, or usefulness of the information contoimd in this report, or that the vra of any information, appamtus, method, or process disclosed in this report may not infringe privately owned rights# or B. Atrumm any Ibbilfties with respect to the use of, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research on the roles of the inherent properties of sand in playing surface stability has been limited to particle-size distribution (Ferguson, 1955;Bingaman and Kohnke, 1970;Adams et al, 1971;Baker et al, 1988;Whitmyer and Blake, 1989) and compressibility (Kezdi, 1979;Waddington, 1992). Dury and Craggs (1977) reported that the playing surface stability of a sports fi eld is aff ected by the size, shape, and particle-size distribution of the medium based on ball bounce ratio.…”
mentioning
confidence: 99%
“…Research on the roles of the inherent properties of sand in playing surface stability has been limited to particle-size distribution (Ferguson, 1955;Bingaman and Kohnke, 1970;Adams et al, 1971;Baker et al, 1988;Whitmyer and Blake, 1989) and compressibility (Kezdi, 1979;Waddington, 1992). Dury and Craggs (1977) reported that the playing surface stability of a sports fi eld is aff ected by the size, shape, and particle-size distribution of the medium based on ball bounce ratio.…”
mentioning
confidence: 99%